The Relationship between Burnout and Compliance with Occupational Safety Implementation in Nurses - Cicci Chairunisa Mas'um; Rismanudin Rismanudin; Nadia Muthia Hanifah Amrin; Muhammad Fathur Rahman Mt Hardjo; Sahari Bulan (Jurnal Ners, 2026)
Burnout among nurses is a significant occupational issue that may negatively affect the quality of healthcare services, including compliance with occupational safety implementation. Poor adherence to occupational safety practices increases the risk of workplace accidents, injuries, and healthcare-associated infections within hospital settings. This study aimed to examine the relationship between burnout and compliance with occupational safety implementation among nurses. A quantitative study with a cross-sectional design was conducted involving 150 nurses selected through proportionate random sampling. Burnout was assessed using the Maslach Burnout Inventory (MBI), while occupational safety compliance was measured using a validated occupational safety compliance questionnaire. Data were analyzed using the Spearman Rank correlation test with a significance level of 0.05. The findings revealed that most respondents experienced moderate burnout (58.7%) and demonstrated good occupational safety compliance (64.0%). A significant negative relationship was found between burnout and compliance with occupational safety implementation (p = 0.002; r = -0.387), indicating that higher burnout levels were associated with lower compliance with occupational safety practices. The study concludes that organizational support and effective workload management are essential strategies to reduce burnout and improve nurses' compliance with occupational safety implementation.